Role of a local transcription factor in governing cellular carbon/nitrogen homeostasis in Pseudomonas fluorescens. Issue 6 (1st March 2021) - Naren, Naran; Zhang, Xue-Xian
Abstract: Autoactivation of two-component systems (TCSs) can increase the sensitivity to signals but inherently cause a delayed response. Here, we describe a unique negative feedback mechanism enabling the global NtrB/NtrC regulator to rapidly respond to nitrogen starvation over the course of histidine utilization ( hut ) in Pseudomonas fluorescens . NtrBC directly activates transcription of hut genes, but overexpression will produce excess ammonium leading to NtrBC inactivation. To prevent this from occurring, the histidine-responsive repressor HutC fine-tunes ntrBC autoactivation: HutC and NtrC bind to the same operator site in the ntrBC promoter. This newly discovered low-affinity binding site shows little sequence similarity with the consensus sequence that HutC recognizes for substrate-specific induction of hut operons. A combination of genetic and transcriptomic analysis indicated that both ntrBC and hut promoter activities cannot be stably maintained in the Δ hutC background when histidine fluctuates at high concentrations. Moreover, the global carbon regulator CbrA/CbrB is involved in directly activating hut transcription while de-repressing hut translation via the CbrAB-CrcYZ-Crc/Hfq regulatory cascade. Together, our data reveal that the local transcription factor HutC plays a crucial role in governing NtrBC to maintain carbon/nitrogen homeostasis through the complex interactions between two TCSs (NtrBC and CbrAB) at the hut promoter.